PENGGUNAAN ABREVIASI DI PESANTREN DAARUT TAUHIID - Anggraeni, Diana (2016)
Penelitian ini dilatarbelakangi oleh penggunaan abreviasi di Pesantren Daarut Tauhiid yang memiliki beragam abreviasi (pemendekan kata) dalam kegiatan dakwahnya. Abreviasi tersebut terdiri atas metode dakwah dan lembaga-lembaga di Pesantren Daarut Tauhiid. Adapun tujuan dari penelitian ini yaitu mendeskripsikan bentuk abreviasi, pola pembentukan, makna abreviasi, dan komponen makna di Pesantren Daarut Tauhiid. Penelitian ini menggunakan metode deskriptif kualitatif. Hasil penelitian ini menunjukkan empat temuan penelitian sebagai berikut. (1) Hasil Persentase bentuk abreviasi yang diperoleh, menunjukkan bahwa bentuk singkatan yang paling mendominasi dalam penggunaan abreviasi di Pesantren Daarut Tauhiid yaitu berjumlah 63, 08%. Bentuk akronim berjumlah 30,8%. Bentuk gabungan singkatan dan akronim berjumlah 6,2%. (2) Hasil persentase pola pembentukan abreviasi yang diperoleh, menunjukkan bahwa dalam bentuk singkatan banyak digunakan pola pembentukan baru yaitu berjumlah 30%, sedangkan akronim berjumlah 23,3%. Gabungan singkatan dan akronim berjumlah 10%. (3) Hasil persentase makna abreviasi yang diperoleh, menunjukkan bahwa makna referensial yang paling mendominasi dalam penggunaan abreviasi di pesantren Daarut Tauhiid yaitu berjumlah 50,8%. Makna ideasional berjumlah 41,5%. Makna emotif berjumlah 7,7%. (4) Hasil persentase komponen makna abreviasi yang diperoleh, menunjukkan bahwa komponen makna budaya yang paling mendominasi dalam penggunaan abreviasi di pesantren Daarut Tauhiid yaitu berjumlah 23,6%. Komponen makna sikap dengan berjumlah 22,7%. Komponen makna pendidikan berjumlah 10,3%. Komponen makna ekonomi dengan jumlah yang sama yaitu 10,3%. Komponen makna sosial berjumlah 8,4%. Komponen makna akhlak berjumlah 7,6%. Komponen makna lembaga dengan jumlah yang sama yaitu 7,6%. Komponen makna ibadah berjumlah 5,7%. Komponen makna materi berjumlah 1,9%. Komponen makna lingkungan berjumlah 0,10%. Komponen makna SDM dengan jumlah yang sama yaitu 0,10%.;---This research is motivated by the use of abbreviation in Daarut Tauhiid boarding schools who have varied abbreviation (shortening of the word) in his missionary endeavor activities. The abbreviation consists of methods of missionary endeavor and institutions in Daarut Tauhiid boarding schools. The purpose of this research is to describe the form of abbreviation, pattern formation, the meaning of abbreviation, and components of meaning in Daarut Tauhiid boarding schools. This research used descriptive qualitative method. The results showed as follows four research findings. (1) The percentage results of abbreviation form earned, shows that the abbreviated form of the most dominates in using abbreviation in Daarut Tauhiid boarding schools amounts to 63,08%. The acronym forms amounts to 30,8%. Combined form of abbreviations and acronyms amounts to 6,2%. (2) The percentage of abbreviation formation pattern is earned, shows that in the form of an abbreviation mostly used pattern is new formation that amounts to 30%, while the acronym amounts to 23,3%. The combined abbreviations and acronyms amounts to 10%. (3) The percentage results of abbreviation meaning is earned, shows that referential of meaning which most dominated abbreviation in usage in Daarut Tauhiid boarding schools which amounts to 50,8%. The percentage results components of meaning abbreviation is earned, shows that referential of meaning which most dominated abbreviation in usage in Daarut Tauhiid boarding schools which amounts to 23,6%. Components of meaning attitude amounts to 22,7%. Components of meaning education amounts to 10.3%. Components of economic meaning for the same amount, that is 10,3%. Components of social meaning amounts to 8,4%. Components of moral meaning amounts to 7,6%. Components of institution meaning with the same amount of 7,6%. Components of meaning of worship amounts to 5,7%. Components of material meaning amounts to 1,9%. Components of environmental meaning amounts to 0,10%. Components of meaning of human resources for the same amount, that is 0,10%.